Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.4314/sajas.v51i5.1
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera leaf meal as a feed supplement for dairy calves

Abstract: The study evaluated the effects of supplements of Moringa oleifera leaf meal (MOLM) on blood biochemistry and growth of pre-weaned Holstein calves (n = 48). Four-day-old calves were blocked (based on order of birth and birth weight) and randomly allocated to three dietary treatments, namely M0: unsupplemented control, M30: supplemented with 8.33 g MOLM /100 kg bodyweight (BW), and M60: supplemented with 16.66 g MOLM /100 kg BW. The experiment ended when the calves were 42 days old. The MOLM was diluted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Immunoglobulin G (Ig) levels: The concentration of Immunoglobulin G (IgG) was assessed using an Enzyme-Linked Immunosorbent Assay (ELISA) kit for bovine IgG. Blood samples were sent to Karachi Lab for analysis (Kekana et al, 2021). Statistical Analysis: The acquired data were statistically evaluated using Analysis of Variance ANOVA in a Completely Randomized Deisgn (Steel et al, 1960), and Duncan's multiple range test was used to assess mean differences for significance (Duncan, 1955).…”
Section: Preparation Of Molmmentioning
confidence: 99%
“…Immunoglobulin G (Ig) levels: The concentration of Immunoglobulin G (IgG) was assessed using an Enzyme-Linked Immunosorbent Assay (ELISA) kit for bovine IgG. Blood samples were sent to Karachi Lab for analysis (Kekana et al, 2021). Statistical Analysis: The acquired data were statistically evaluated using Analysis of Variance ANOVA in a Completely Randomized Deisgn (Steel et al, 1960), and Duncan's multiple range test was used to assess mean differences for significance (Duncan, 1955).…”
Section: Preparation Of Molmmentioning
confidence: 99%
“…Previous studies have shown that improving dam diets during the dry period, particularly with herbs, may positively affect colostrum yield and quality (Hosoda et al, 2005;Smeti et al, 2015;Kozyr et al, 2019). Herbal supplements such as MOLM when mixed with feed enhance and add flavors in animal feed, and therefore, influence eating patterns, secretion of digestive fluids, and total feed intake (Bhatt, 2015;Kekana et al, 2021). However, in this study, the DMI, BW change, BCS, and colostrum yield were not affected by supplementation of MOLM as observed in the previous studies (Kekana et al, 2020(Kekana et al, , 2019.…”
Section: Dams' Responses To Molmmentioning
confidence: 99%
“…Herbal plants such as Moringa oleifera have been extensively investigated in ruminants' nutrition because of their relatively high biomass yield, high nutritional quality, and low cost of production (Kekana, 2014;Kholif et al, 2016;Falowo et al, 2018;Kekana et al, 2019Kekana et al, , 2020Kekana et al, , 2021. Moringa oleifera (family Moringaceae) is an evergreen tree fodder and a promising alternative nutrient source in diets for ruminants and its by-products (Falowo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants have developed several adaptive strategies in response to abiotic stresses, such as temperature fluctuations, osmotic stress, and dehydration [ 8 , 9 ]. These adaptive alterations include biochemical, physiological, and molecular changes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%